Oral Candida albicans Induced Murine Oral Candidiasis - Kiyoura, Yusuke; Shirai, Yayoi; Seino, Akinori; Suzuki, Nao; Kamata, Masayoshi (Ronen Shika Igaku, 2005)
Candida albicans is often isolated from the oral cavity of the elderly. However, the pathogenicity of C. albicans present in the oral cavity of the elderly has not been clarified. In the present study of oral candidiasis, the pathogenicity of C. albicans was investigated in vivo using a mouse model. The results showed that all strains isolated from the oral cavity of the elderly induced candidiasis. Tongue fur formed on the surface of the mouse tongue three days after inoculation. Further, the number of residual C. albicans cells in the oral cavity ranged from 1.58±0.54×104 to 18.66±5.69×104.The results of the present study suggest the possibility that C. albicans in the oral cavity induces candidiasis in the elderly, who have reduced immunity. Therefore, it is necessary to control C. albicans colonization through everyday oral care as much as possible in compromised hosts, such as the elderly requiring care.